2011
DOI: 10.1103/physrevd.83.095012
|View full text |Cite
|
Sign up to set email alerts
|

Testing theCP-violating MSSM in stau decays at the LHC and ILC

Abstract: We study CP violation in the two-body decay of a scalar tau into a neutralino and a tau, which should be probed at the LHC and ILC. From the normal tau polarization, a CP asymmetry is defined which is sensitive to the CP phases of the trilinear scalar coupling parameter A , the gaugino mass parameter M 1 , and the Higgsino mass parameter , in the stau-neutralino sector of the minimal supersymmetric standard model. Asymmetries of more than 70% are obtained in scenarios with strong stau mixing. As a result, dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…[49][50][51][52] and references therein for studies of CP-violating effects at the LHC via rate asymmetries or triple products. While in some cases CP-violating effects occur already at tree-level, it is important to take into account also loop-induced CP-violating effects.…”
Section: Jhep05(2013)053mentioning
confidence: 99%
“…[49][50][51][52] and references therein for studies of CP-violating effects at the LHC via rate asymmetries or triple products. While in some cases CP-violating effects occur already at tree-level, it is important to take into account also loop-induced CP-violating effects.…”
Section: Jhep05(2013)053mentioning
confidence: 99%
“…Thus, triple product asymmetries have been proposed in many theoretical papers. For the Large Hadron Collider (LHC), triple product asymmetries have been studied for the decays of neutralinos [22][23][24], stops [13,[25][26][27], sbottoms [28,29], and staus [30]. In a Monte Carlo (MC) analysis for stop decays [26,27], it could be shown that the decay chain can be reconstructed and asymmetries be measured at a 3σ level for luminosities of the order of 300 fb −1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have been completed to measure the absolute value of A t and are expected to be accurate to within 10% [30,31]. Also, there is the potential to study the CP properties of other 3rd generation trilinear couplings, namely those of theτ sector, φ Aτ [32,33]. In addition, these studies may also be applicable to the LHC if tau polarisation can be probed in the final state [34].…”
Section: Introductionmentioning
confidence: 99%